Intergovernmental planning and its impact on the implementation of Intergrated Development Plan: a case study on Makhado local municipality - Mulaudzi, Marubini Maryjane (My University, 2008)
ABSTRACT Local government is the sphere closest to the people and is described as the most important sphere of government. The end of apartheid in the early 1990s has left South Africa with permanent social and economic legacy which is characterised by racial division and discrimination. Over the last decade all local government institutions in South Africa had been totally restructured and transformed into a single uniformed system of local governance in which all municipalities area given a new status, new powers and functions and a new constitutionally entrenched vision of achieving specific municipal objects and to be generally developmental in nature (Bekink, 2006). Most important shifts in direction for local government are enshrined in Chapter 7 of the Constitution (Act 108 of 1996), which provides the objectives of local government as being to provide a democratic and accountable government for local communities and to encourage the involvement of stakeholders, including the communities in the matters of local government. This marks the difference between the new form of local government and that of the past. The new local government has a dynamic developmental role to ensure maximum impact on poverty alleviation and to address socio-economic inequalities. Local government cannot achieve their new goals on their own. They need the support and assistance of the two higher spheres of government. This is because developmental local government requires a system of intergovernmental planning in the decision-making of local development. This entails mutual understanding with inclusive decision-making between government spheres, private sector and communities. This needs to take place within the framework of Integrated Development Planning. Therefore, stakeholder involvement in the IDP process is relevant. Over the past few years in the democratic South Africa, local government has seemed to reflect a system of government characterised by low levels of service delivery by local authorities, lack of transparency in decision making and inability to participate in municipal affairs. Various efforts have been made to bring about a system of co-operative governance to enhance intergovernmental planning, economic regeneration and social reconciliation in South Africa’s municipalities. In general, the results thus far have been somewhat mixed, but as case-study evidence (chapter 4) suggest, it is clear that some significant improvements have taken place in municipalities, particularly in terms of the implementation of the IDP. This study was undertaken in an effort to assess the extent to which intergovernmental planning plays a role in the IDP implementation of Makhado LM.
Keywords: Makhado local municipality; Integrated Development Plan